For a Future Free of Violence: Moral Competencies As a Means of Emancipation and Self-Empowerment - Dutka, Joanna (ETHICS IN PROGRESS, 2018)
The paper explores the role of fostering moral-democratic competencies for violence prevention, in particular in the relation to genderbased, intimate partner and domestic violence. Additionally, significant emphasis is placed on the prevention of revictimisation. Violence prevention is framed with regard to the political importance of violence-free homes and intimate relationships for the empowerment of women. The paper refers to the complex situation of women subjected to abuse and the effects of violence on an individual. As a countermeasure, the paper proposes the development of moral-democratic competencies, and recommends the Konstanz Method of Dilemma Discussion® as an example of an efficient method to accomplish this task.